1996
DOI: 10.1002/(sici)1098-2337(1996)22:6<457::aid-ab6>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Life spans in mice from strains selected for high or low aggression

Abstract: The present study assessed the life spans in two lines of mice selectively bred for high (Turku Aggressive, TA) and low (Turku Nonaggressive, TNA) levels of aggression. The maintained parental Swiss albino strain (N), normally distributed with regard to aggression, served as a control line. It was found that the TNA males had a significantly shorter life span than the other lines of mice of both sexes. The relative early death of the TNA males was discussed in terms of male age‐related decline of inherited low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…First, longevity varies with personality (Cavigelli and McClintock, 2003;Cavigelli et al, 2009;Ewalds-Kwist and Selander, 1996), suggesting a cumulative cost to personality. In LAL-SAL mice for example, young LAL mice have a higher antioxidant capacity than SAL mice yet their oxidative stress levels are not lower, and ultimately they have shorter life spans (Costantini et al, 2008a;Ewalds-Kwist and Selander, 1996). To achieve the same level of oxidative stress, therefore, young LAL mice may up-regulate their antioxidant system, an additional investment that may be costly in later life (Costantini et al, 2008a).…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…First, longevity varies with personality (Cavigelli and McClintock, 2003;Cavigelli et al, 2009;Ewalds-Kwist and Selander, 1996), suggesting a cumulative cost to personality. In LAL-SAL mice for example, young LAL mice have a higher antioxidant capacity than SAL mice yet their oxidative stress levels are not lower, and ultimately they have shorter life spans (Costantini et al, 2008a;Ewalds-Kwist and Selander, 1996). To achieve the same level of oxidative stress, therefore, young LAL mice may up-regulate their antioxidant system, an additional investment that may be costly in later life (Costantini et al, 2008a).…”
Section: Introductionsupporting
confidence: 76%
“…This pattern of high OXY but equivalent OS has also been observed by Costantini and colleagues (Constantini et al, 2008a) when considering aggression in mice, but at the slow (passive) extreme of that trait. Passive mice also have shorter life spans (Ewalds-Kwist and Selander, 1996) and show greater hormonal stress responsiveness than aggressive mice (Veenema et al, 2003). Unifying these studies, Costantini and colleagues suggest that the higher antioxidant capacity in stress-responsive LAL mice may in fact be a surplus, buffering against short-term, stressinduced increases in pro-oxidant production (Constantini et al, 2008a).…”
Section: Discussionmentioning
confidence: 99%
“…Less aggressive male mice have shorter lifespans, and it has been suggested that the age-related decline in the concentrations of catecholamines and testosterone might be responsible for their reduced longevity (Ewalds-Kwist & Selander 1996). Given the present results and the fact that OS may modulate ageing (Harman 1956;Beckman & Ames 1998), the redox status could explain the differences in lifespan that different personalities experience (Cavigelli & McClintock 2003).…”
Section: Discussionmentioning
confidence: 64%
“…The mice were then given access to preweighed food for a period of 72 hr, after which the remaining food and bedding were reweighed. The difference between the preweighed food and the remaining food was the measure of food intake (Ewalds- Kvist & Selander, 1996;Hansen & Ferreira, 1986). By comparing the weight of the bedding in the cage before and after the test period, a measure of excretion (i.e., defecation and urination) was established (Ewalds- Kvist & Selander).…”
Section: Methodsmentioning
confidence: 99%